Structural and dielectric properties of B2O3/Li2O-added Ba0.6Sr0.4TiO3 multilayer ceramics for tunable devices. Issue 3 (15th February 2020) - Lee, Woong-Hee; Im, Mir; Choi, Boo-Hyun; Kweon, Sang-Hyo; Jo, Sora; Sanghadasa, Mohan; Nahm, Sahn
Abstract: B2 O3 and Li2 O (B/L)-added Ba0.6 Sr0.4 TiO3 (BST) ceramics sintered at 940 °C exhibited a dense microstructure with large grains. The amount of B/L additive was 4.5 wt% with a B/L ratio of 1.5:1. The B/L-related liquid phase assisted the densification of the BST ceramics. This BST ceramic displayed a large dielectric constant ( ε r ) of 2834 with a low dielectric loss (tan δ ) of 0.21% at 1.0 MHz. It also displayed a large tunability (28.2% at 10 kV/cm) and a high figure of merit ( FOM ) of 134. BST thick-films were synthesized using the tape casting method. The thick-film densified at 940 °C exhibited a large tunability of 18.7% at 10.0 kV/cm and an FOM of 208; these are higher than the values reported in the literature. Multilayer ceramics (MLCs) consisting of five layers of 40-μm-thick BST thick-films and Ag electrodes were also fabricated at 940 °C. No diffusion occurred between the Ag electrode and BST thick-film. A large tunability of 67.6% at 52 kV/cm with a high FOM of 294 was obtained from this MLC. This verified that the B/L-added BST ceramic is effective for application in tunable multilayer devices.